Cone-Like Rectification Properties of cGMP-Gated Channels in Transmutated Retinal Photoreceptors of Nocturnal Geckoes - Vittorio Vellani; Chiara Giacomoni (The Scientific World Journal)
Photoreceptors of nocturnal geckoes are scotopic, with rod-shaped outer segments, and sensitivities to light similar to the one of retinal rods from other species of lower vertebrates. However, these cells are not rods, but they originated from cones of ancestral diurnal geckoes with pure-cone retinas, after being forced to adapt to a nocturnal behavior. Several interesting adaptations of these rod-like cones have been studied to date; molecular biology and functional studies confirmed that several proteins of the phototransductive cascade display structural and functional properties that indicate their origin from cones rather than from rods. In this paper, we investigate, with whole cell voltage clamp in the photoreceptor detached outer segment preparation, the voltage rectification properties of cGMP-gated channels in three species, Gekko gecko, Tarentola mauritanica, and Hemidactylus frenatus. We show that the current-voltage properties in the physiological voltage range are reminiscent of the ones of cGMP-gated channels from cones rather than from rods of other cold-blooded vertebrates. The origin and the relevance of the mechanisms investigated are discussed.